Local Heat Therapy to Accelerate Recovery After Exercise-Induced Muscle Damage. Issue 4 (October 2020) - Kim, Kyoungrae; Monroe, Jacob C.; Gavin, Timothy P.; Roseguini, Bruno T.
Abstract : The prolonged impairment in muscle strength, power, and fatigue resistance after eccentric exercise has been ascribed to a plethora of mechanisms, including delayed muscle refueling and microvascular and mitochondrial dysfunction. This review explores the hypothesis that local heat therapy hastens functional recovery after strenuous eccentric exercise by facilitating glycogen resynthesis, reversing vascular derangements, augmenting mitochondrial function, and stimulating muscle protein synthesis. Abstract : Local heat therapy hastens recovery after eccentric exercise.